Expression of βhpmeh gene in transgenic events of the potato variety Desiree increases resistance to bacterial wilt caused by Ralstonia solanacearum - Izarra, M.; Gutarra, L.; Fernández, E.; Huamán, E.; Ghislain, M.; Kreuze, Jan F. (2026)
Bacterial wilt, caused by the Ralstonia solanacearum species complex (RSSC), severely affects many important crops and significantly limits potato production worldwide. RSSC bacteria can regulate the expression of their virulence factors, including extracellular polysaccharides and endoglucanases, through quorum sensing, which enables bacteria to sense their population density through signaling molecules and collectively switch on virulence factors when a threshold density is reached. 3-hydroxy palmitic acid methyl ester is the main quorum-sensing molecule in RSSC that can be hydrolyzed by β-hydroxypalmytate methyl ester hydrolase (βHPMEH). In this study, we evaluated the ability of βhpmeh transgenic plants of the potato variety Desiree to reduce bacterial wilt symptoms after artificial inoculation with two RSSC strains virulent on potato under controlled conditions and relate it to the expression of the βhpmeh gene. For each transgenic event, we analyzed the phenotypic response (wilt incidence, latent infection, and area under the disease progress curve). Real-time quantitative PCR was performed to determine the relative expression levels of βhpmeh in transgenic events. Several transgenic events were identified with reduced susceptibility to bacterial wilt compared to Desiree, and a resistance level similar or higher to that of potato variety Cruza 148, which is the most resistant variety available, and which was positively correlated with βhpmeh expression.